(untitled) (Bangladesh Journal of Obstetrics & Gynaecology, 2019)
Objective: The aim of the study was to explore the surgical outcomes of total laparoscopic hysterectomy. Materials and methods: This was a prospective analysis of total Laparoscopic Hysterectomy (TLH) done between January, 2012 to December, 2018 in Shaheed Suhrawardy Medical College and Hospital. Demographic data, clinical criteria, intra operative and postoperative outcome data were recorded. Data were collected in a predesigned Data collection sheet. Follow up records done during discharge from the hospital, one week and four weeks postoperatively. Results: Total 298, laparoscopic hysterectomy were performed during the period. Among them 96 % (n=286) for benign and 4 %( n=12) for malignant condition were included in the study population. Mean age of the patients was 45.4 ± 5.6 years, mean parity was 1.9 ± 0.64 and the mean body mass index was 27.48 ± 0.57. The most common benign disease was leiomyoma, 51.7 %. Among the study cases 21.8% (n=65) had history of at least one previous abdomino-pelvic surgery. Maximum size of uterus removed was 28 weeks and maximum patients, 48% (n=143) had uterine size of 10-14 weeks. The operating time was variable between 50 min to 180 min and in the course of time, the mean operating time dropped from 130 min to 60 min. The mean length of hospital stay was 2 days and the return to normal activities was within 2 weeks. Major complications observed among 3.7 % of cases among them 2(0.67%) bladder injury, 2(0.67%) vesico-vaginal fistula (VVF), 3(1.0%) ureterovaginal fistula (UVF) and 4(1.3%) peroperative hemorrhage requiring blood transfusion. Among the 7 cases of urological complications, one patient with VVF and one patient with UVF needed relaparotomy. Ultimately all cases were managed without any residual problem. Conversion to laparotomy was 0.3 % (n=1) of case. Conclusion: TLH offers the benefit of minimally invasive surgery to the patient and is a safe and acceptable alternative to standard hysterectomy for various gynaecological indications. Bangladesh J Obstet Gynaecol, 2019; Vol. 34(1): 28-35